Optical Coherence Tomography in Mild Cognitive Impairment: A Systematic Review and Meta-Analysis - Mejia-Vergara, Alvaro J.; Restrepo-Jimenez, Paula; Pelak, Victoria S. (Frontiers in Neurology, 2020)
Purpose: The use of optical coherence tomography (OCT) of the retina to detect retinal degeneration is being investigated as potential biomarker for Mild Cognitive Impairment (MCI) and Alzheimer’s disease (AD).An overwhelming body of evidence indicates that the discovery of disease-modifying treatments for AD should be aimed at the pre-dementia clinical stage of AD, i.e. MCI. We aimed to perform systematic review and meta-analysis on retinal OCT in MCI. Methods: We performed a systematic review of the literature in three databases (PUBMED, EMBASE, and LATINDEX) for studies that measured retinal thickness using OCT in MCI and healthy controls, age 50 or older, between January 1, 2000, and July 31, 2019. Cohort and case-control studies were reviewed. We calculated the effect size for studies in the review that met the following criteria: 1) statistically significant difference between MCI subjects and normal controls for several OCT variables, 2) use of spectral-domain OCT and 3) use of APOSTEL recommendations for OCT reporting. Weighted Hedges’ g statistic calculated the pooled effect size for four variables: Ganglion Cell Layer – Inner Plexiform Layer (GCL-IPL) Complex thickness in micrometers (um), Circumpapillary Retinal Nerve Fiber Layer (pRNFL) thickness in um, Macular thickness in um, and Macular volume in um3. For variables with high heterogeneity, multivariate meta-regression was performed. We followed the PRISMA guidelines for systematic reviews. Results: Fifteen articles met the inclusion criteria. Total of 58.9% of MCI patients had statistically significant thinning of the pRNFL compared to normal subjects, while 61.6% of all MCI patients who had macular volume measured had a statistically significant reduction in volume compared to controls, and 50.0% of the macular GCL-IPL complexes measured demonstrated significant thinning in MCI compared to normal controls. The meta-analysis demonstrated a large effect size for decreased macular thickness in MCI compared to normals, but there was substantial heterogeneity. The other variables did not demonstrate significant differences and had substantial heterogeneity. Meta-regression analysis did not reveal an explanation. Conclusions: Better understanding of the cause of retina degeneration and longitudinal, standardized studies are needed to determine if OCT can be used as a biomarker for MCI due to AD.